How changes in cropping intensity affect water usage in an irrigated Mediterranean catchment - Duarte, A.C. (2021)
Agricultural policies and social change influence irrigation management decisions and their associated effects. The changes in the Common Agricultural Policy of the European Union have deeply affected irrigated agriculture in the Mediterranean region. In this region, hydrology is rather complex and the environment particularly vulnerable. We monitored cropping patterns and the water balance in a sprinkler-irrigated catchment in Central Portugal over thirteen irrigation seasons and twelve rainfall seasons. There was wide variation in annual rainfall (from 283 mm to 667 mm) and in the intensity of rainfall events from year to year. A monitoring station at the catchment outlet was installed to measure runoff which, together with field observations, allowed us to compute a water balance for both the rainfed and the irrigation seasons. Changes in cropping intensity led to changes in the depth of irrigation. Irrigation runoff followed irrigation depth and both followed the trend of cropping intensity. Less intensive cropping also reduced the off-site effects of agricultural activities. The runoff coefficient was 0.28 in the rainfed seasons and 0.02 in the irrigation seasons. The changes in the irrigation hydrology and in the off-site effects of agricultural activities in the catchment were caused by changes in cropping intensity induced by the European Union Common Agricultural Policy reforms, rather than by environmental or technical factors.